2015
DOI: 10.1007/s10646-015-1540-7
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic insights into tetracycline effects on microbial community and antibiotic resistance of mouse gut

Abstract: Antibiotics have been widely used for disease prevention and treatment of the human and animals, and for growth promotion in animal husbandry. Antibiotics can disturb the intestinal microbial community, which play a fundamental role in animals' health. Misuse or overuse of antibiotics can result in increase and spread of microbial antibiotic resistance, threatening human health and ecological safety. In this study, we used Illumina Hiseq sequencing, (1)H nuclear magnetic resonance spectroscopy and metagenomics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 50 publications
8
34
0
Order By: Relevance
“…It is unclear if this is a reflection of limited bioavailability of TC, use of an already established community in the assay, and/or fewer bacterial generations studied. Selection of tetA was also observed in the fecal bacterial communities of mice given water supplemented with 10 mg/L TC compared to control mice (Yin et al, 2015). Selection of tetG did not occur in this case, which might be related to e.g.…”
Section: Discussionmentioning
confidence: 70%
“…It is unclear if this is a reflection of limited bioavailability of TC, use of an already established community in the assay, and/or fewer bacterial generations studied. Selection of tetA was also observed in the fecal bacterial communities of mice given water supplemented with 10 mg/L TC compared to control mice (Yin et al, 2015). Selection of tetG did not occur in this case, which might be related to e.g.…”
Section: Discussionmentioning
confidence: 70%
“…Huang et al used high-throughput sequencing to detect the change in bacterial diversity in different bioreactors with and without tetracycline [20]. Yin et al used Illumina Hiseq sequencing approaches to explore the intestinal microbial community shift and antibiotic resistance alterations in mice taking antibiotics [21]. In this research, authors adopted a MiSeq high-throughput sequencing method based on second generation high-throughput sequencing technology to analyze the 16S rDNA sequences of the samples, to detect the dominant species, the rare species and some unknown species at the same time and to probe the microbial community composition and bacterial relative abundance.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, animal manure is considered a hotspot for the spread of ARGs and MGEs to the environment . Antibiotic administration is one of the major factors influencing the abundance and diversity of ARGs in animals . Looft et al .…”
Section: Metagenomic Exploration Of Argsmentioning
confidence: 99%
“…30,31 Antibiotic administration is one of the major factors influencing the abundance and diversity of ARGs in animals. 88 Looft et al 23,84 investigated the effects of in-feed sublethal antibiotics (i.e., ASP250, an antibiotic feed additive containing chlortetracycline, sulfamethazine, and penicillin) on swine intestinal microbiome ARGs. Analysis of the metagenomes revealed that, despite a high background of ARGs in nonmedicated swine, the abundance and diversity of ARGs increased in the medicated swine microbiome after 14 days of antibiotic treatment; indirect selection of aminoglycoside O-phosphotransferases conferring resistance to antibiotics that were not applied was also observed.…”
Section: Metagenomic Exploration Of Argsmentioning
confidence: 99%